Pyriproxyfen Netting Suppresses Reproductive Output and Oviposition in Anopheles Stephensi - Alla Abd AL Hassan AL Hilfy (Academia Open, 2026)
General Background: Insecticide resistance among malaria vectors poses a critical threat to global disease control strategies. Specific Background: Pyriproxyfen, a juvenile hormone analogue, interrupts insect growth and reproduction through sublethal contact. Knowledge Gap: The combined effects of pyriproxyfen-treated netting on adult fecundity, egg hatchability, and oviposition choice in Anopheles stephensi remain insufficiently characterized. Aims: This study evaluated reproductive performance and behavioral deterrence in adult females following exposure to pyriproxyfen-treated netting. Results: Exposure to 0.02 ppm pyriproxyfen reduced egg production by 80.7% and hatchability to 18.5%, while choice assays demonstrated 98.5% effective repellency. Novelty: The findings demonstrate a synergistic dual mechanism combining severe physiological sterilization with near-complete behavioral oviposition deterrence. Implications: Incorporating pyriproxyfen into long-lasting insecticidal nets provides an effective strategy to suppress resistant vector populations. Keywords: Anopheles Stephensi, Insect Growth Regulator, Oviposition Deterrence, Pyriproxyfen, Vector Control Key Findings Highlight Short contact with treated netting reduced female egg production by up to 80.7 percent. Sublethal exposure decreased egg hatchability down to 18.5 percent at 0.02 ppm. Choice bioassays revealed an effective oviposition repellency rate reaching 98.5 percent.